Treatment of aggressive T-cell lymphoma/leukemia with anti-CD4 CAR T cells - Feng, Jia; Xu, Haichan; Cinquina, Andrew; Wu, Zehua; Zhang, Wenli; Sun, Lihua; Chen, Qi; Tian, Lei; Song, Le; Pinz, Kevin G.; Wada, Masayuki; Jiang, Xun; et al. (Frontiers in Immunology, 2022)
T-cell lymphomas are aggressive lymphomas that often resist current therapy options or present with relapsed disease, making the development of more effective treatment regimens clinically important. Previously, we have shown that CD4 CAR can effectively target T-cell malignancies in preclinical studies. As IL-15 has been shown to strengthen the anti-tumor response, we have modified CD4 CAR to secrete an IL-15/IL-15sushi complex. These CD4-IL15/IL15sushi CAR T cells and NK92 cells efficiently eliminated CD4+ leukemic cell lines in co-culture assays. Additionally, CD4-IL15/IL15sushi CAR out-performed CD4 CAR in in vivo models, demonstrating a benefit to IL-15/IL-15sushi inclusion. In a Phase I clinical trial, CD4-IL15/IL15sushi CAR T cells were tested for safety in three patients with different T-cell lymphomas. Infusion of CD4-IL15/IL15sushi CAR T cells was well-tolerated by the patients without significant adverse effects and led to the remission of their lymphomas. Additionally, infusion led to the depletion of CD4+ Treg cells and expansion of CD3+CD8+ T cells and NK cells. These results suggest that CD4-IL15/IL15sushi CAR T cells may be a safe and effective treatment for patients with relapsed or refractory T-cell lymphomas, where new treatment options are needed.